Enhancing Taekwondo performance: The role of pre-kicking techniques and stimulus triggers in elite athletes - Everard, S.; Chang, M.; Landeo, R. (Journal of Sports Sciences, 2025)
This study evaluated the impact of pre-kicking techniques and stimulus triggers on kick performance in Taekwondo, a sport known for its fast pace and emphasis on offensive moves. Data from 20 elite athletes, including Olympians and a world champion, were collected using three-dimensional (3D) motion capture and force plates. The athletes performed kicks under various conditions, combining passive or dynamic triggers with static or bouncing-in-place pre-kicking modes. The results showed that a quieter (static) pre-kicking stance led to shorter reaction times, while pre-kicking bouncing-in-place increased foot peak velocities. Dynamic stimulus triggers enhanced both reaction time and foot peak velocity, however, their effect on take-off velocity was not significant. The results underscore the complex interplay between various factors in Taekwondo performance and highlight that coaches and athletes need to consider a strategic balance between training and techniques that enhance reaction speed and/or power.